A meta-analysis of shared leadership and team effectiveness. - Wang, Danni; Waldman, David A.; Zhang, Zhen (Journal of Applied Psychology, 2014)
A growing number of studies have examined the "sharedness" of leadership processes in teams (i.e., shared leadership, collective leadership, and distributed leadership). We meta-analytically cumulated 42 independent samples of shared leadership and examined its relationship to team effectiveness. Our findings reveal an overall positive relationship (ρ = .34). But perhaps more important, what is actually shared among members appears to matter with regard to team effectiveness. That is, shared traditional forms of leadership (e.g., initiating structure and consideration) show a lower relationship (ρ = .18) than either shared new-genre leadership (e.g., charismatic and transformational leadership; ρ = .34) or cumulative, overall shared leadership (ρ = .35). In addition, shared leadership tends to be more strongly related to team attitudinal outcomes and behavioral processes and emergent team states, compared with team performance. Moreover, the effects of shared leadership are stronger when the work of team members is more complex. Our findings further suggest that the referent used in measuring shared leadership does not influence its relationship with team effectiveness and that compared with vertical leadership, shared leadership shows unique effects in relation to team performance. In total, our study not only cumulates extant research on shared leadership but also provides directions for future research to move forward in the study of plural forms of leadership.